Interdisciplinary integration of nursing and psychiatry (INaP) for the treatment of dizziness. (26th November 2019) - Gerretsen, Philip; Shah, Parita; Logotheti, Anastasia; Attia, Mohamed; Balakumar, Thushanthi; Sulway, Shaleen; Ranalli, Paul; Dillon, Wanda A.; Pothier, David D.; Rutka, John A.
Abstract : Objectives: The traditional medical care model of "assess and refer" requires revamping to address the multifaceted needs of patients with chronic dizziness and imbalance by adopting an interdisciplinary approach to care that integrates nursing and psychiatry (INaP). We aim to present a novel interdisciplinary approach that incorporates INaP in the care of patients with chronic dizziness and imbalance. Methods: Presentation of an interdisciplinary model of care that incorporates INaP provided at the Toronto General Hospital in Toronto, Canada. Results: Interdisciplinary care incorporating INaP, which includes the provision of support from an interdisciplinary health care team (ie, neurotologist, neurologist, psychiatrist, physiotherapist, and nurse clinician), psychoeducation about the interaction between chronic dizziness and psychiatric comorbidities, and ongoing access to medical and psychosocial assessment and intervention, addresses the physical and emotional aspects of patients' experience with chronic dizziness. Conclusions: The novel comprehensive interdisciplinary approach incorporating INaP may be more effective than interdisciplinary care without INaP in improving clinical outcomes in patients with chronic dizziness. In the subsequent study, we present data comparing patients treated for chronic dizziness and imbalance with and without the integration of INaP in an interdisciplinary setting. Level of Evidence: 5 Laryngoscope, 130:1792–1799, 2020